2010
DOI: 10.4314/tzool.v7i1.52087
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzymes in the gut of the elephant snout fish, <i>Mormyrus rume<//i> (Valenciennes, 1846) (Osteichthys: Mormyridae)

Abstract: Qualitative and quantitative assays were conducted to determine the occurrence and distribution of digestive enzymes in different gut regions of juvenile and adult elephant snout fish, Mormyrus rume. Amylase, maltase, lactase, sucrase, chitinase, pepsin, trypsin and lipase were present in the oesophagus, stomach, pyloric caeca, duodenum, ileum and rectum at varying quantities and activities. The wide distribution of enzymes in both juvenile and adult M. rume confirms its ability to digest carbohydrate, protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
2
6
1
Order By: Relevance
“…This could indicate that the digestion of carbohydrate foods was concluded in these parts of the alimentary canal (AC). A similar result was presented in the study of Odedeyi and Fagbenro, (2010).…”
Section: Discussionsupporting
confidence: 89%
“…This could indicate that the digestion of carbohydrate foods was concluded in these parts of the alimentary canal (AC). A similar result was presented in the study of Odedeyi and Fagbenro, (2010).…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that during starvation, the digestive enzymes vary in activity pattern in different fish, such as hybrid tilapia juveniles ( Oreochromis niloticus × O. aureus ) (Wang et al, 2010) and Gammarus fossarum (Charron et al, 2014). This may be related to the growth stage (Xiu‐Juan et al, 2009), feeding habit (Ded Eyi & Fagbenro, 2010), starvation duration (Wang et al, 2010) and environmental temperature (Hofer, 1979). In this experiment, grouper performed decreased trypsin, lipid and amylase activities after prolonged starvation.…”
Section: Discussionmentioning
confidence: 99%
“…However, during improper storage, protein is rapidly degraded, via a process mediated by indigenous and microbial proteases. Chymotrypsin, cathepsins, trypsin, lipase, and phospholipase are reportedly found in the hepatopancreas, spleen, and pyloric ceca of seafood, whereas pepsin is located in the stomach (Odedeyi & Fagbenro, ). Belly burst, which commonly occurs in fish, is a function of the enzymes in the fish gut, causing rapid protein decomposition.…”
Section: Seafood Spoilagementioning
confidence: 99%